Last visit was: 14 Jul 2024, 22:12 It is currently 14 Jul 2024, 22:12
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Date
Tags:
Difficulty: 605-655 Level,    Sequences,                               
Show Tags
Hide Tags
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [134]
Given Kudos: 85011
Send PM
Most Helpful Reply
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [51]
Given Kudos: 85011
Send PM
User avatar
Manager
Manager
Joined: 25 Sep 2012
Posts: 203
Own Kudos [?]: 566 [13]
Given Kudos: 242
Location: India
Concentration: Strategy, Marketing
GMAT 1: 660 Q49 V31
GMAT 2: 680 Q48 V34
Send PM
General Discussion
Tutor
Joined: 16 Oct 2010
Posts: 15108
Own Kudos [?]: 66634 [5]
Given Kudos: 436
Location: Pune, India
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
4
Kudos
1
Bookmarks
Expert Reply
b2bt wrote:
Lets assume the first two terms to be x and y
Then rest of the numbers in the series will be x, y, x+y, x+2y, 2x+3y, 3x+5y, 5x+8y, ...

A.) (3x+5y) - (x+2y) = 5
2x+3y = 5 which is indeed the fifth term

SUFFICIENT

B.) (3x+5y) +(5x+8y) = 21
8x+13y = 21
its the 8th term

INSUFFICIENT

Answer - A
Difficulty - 650
Time taken - 1:59


Or you can simply say that the terms are t1, t2, ....

(1) The 6th term of S minus the 4th term equals 5.
t6 - t4 = 5
But t6 = t4 + t5
t6 - t4 = t5 = 5
Sufficient

(2) The 6th term of S plus the 7th term equals 21.
t6 + t7 = 21
t6 + t6 + t5 = 21
We don't know t6 and hence we cannot find t5.
Not sufficient

Answer (A)
Director
Director
Joined: 22 Feb 2018
Posts: 784
Own Kudos [?]: 1059 [0]
Given Kudos: 135
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Bunuel wrote:
SOLUTION

In the sequence S of numbers, each term after the first two terms is the sum of the two immediately preceding terms. What is the 5th term of S?

\(s_n=s_{n-1}+s_{n-2}\), for \(n>2\).

(1) The 6th term of S minus the 4th term equals 5 --> \(s_6-s_4=5\) --> \((s_5+s_4)-s_4=5\) --> \(s_5=5\). Sufficient.

(2) The 6th term of S plus the 7th term equals 21 --> \(s_6+s_7=21\) --> \(s_6+(s_6+s_5)=21\). Since we don't know \(s_6\) we cannot find \(s_5\). Not sufficient.

Answer: A.



Can anyone please explain how S7 = S6+S5 as i did not get it?

Instead of x, y, x+y, x+2y, 2x+3y, 3x+5y, 5x+8y, ..., Can i consider x,y, x+y, 2x+y, 2x+2y, 4x+3y,4x+4y?
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [0]
Given Kudos: 85011
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Expert Reply
Raxit85 wrote:
Bunuel wrote:
SOLUTION

In the sequence S of numbers, each term after the first two terms is the sum of the two immediately preceding terms. What is the 5th term of S?

\(s_n=s_{n-1}+s_{n-2}\), for \(n>2\).

(1) The 6th term of S minus the 4th term equals 5 --> \(s_6-s_4=5\) --> \((s_5+s_4)-s_4=5\) --> \(s_5=5\). Sufficient.

(2) The 6th term of S plus the 7th term equals 21 --> \(s_6+s_7=21\) --> \(s_6+(s_6+s_5)=21\). Since we don't know \(s_6\) we cannot find \(s_5\). Not sufficient.

Answer: A.



Can anyone please explain how S7 = S6+S5 as i did not get it?

Instead of x, y, x+y, x+2y, 2x+3y, 3x+5y, 5x+8y, ..., Can i consider x,y, x+y, 2x+y, 2x+2y, 4x+3y,4x+4y?


The stem says that each term after the first two terms is the sum of the two immediately preceding terms. So, the seventh term \(s_7\) equals to the sum of the two immediately preceding terms, which are \(s_5\) and \(s_6\): \(s_7=s_6+s_5\).

If you consider the first term to be x and the second term to be y, then:
1st term = x;
2nd term = y;
3rd term = x + y;
4th term = y + (x + y) = 2y + x;
5th term = (x + y) + (2y + x) = 3y + 2x;
...
Intern
Intern
Joined: 03 Dec 2017
Posts: 23
Own Kudos [?]: 12 [0]
Given Kudos: 75
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Bunuel wrote:

The stem says that each term after the first two terms is the sum of the two immediately preceding terms. So, the seventh term \(s_7\) equals to the sum of the two immediately preceding terms, which are \(s_5\) and \(s_6\): \(s_7=s_6+s_5\).

If you consider the first term to be x and the second term to be y, then:
1st term = x;
2nd term = y;
3rd term = x + y;
4th term = y + (x + y) = 2y + x;
5th term = (x + y) + (2y + x) = 3y + 2x;
...


okay so i did this
6th term = 3x + 5y
7th term = 5x + 8y

St1 -- 6th - 4th = 5
3x + 5y - x - 2y => 2x + 3y = 5 --looks like x n y should be 1

St2 -- 6th + 7th = 21
3x + 5y +v5x + 8y => 8x + 13y = 21 --looks like x n y should be 1

could you please let me know why above is wrong ?
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [0]
Given Kudos: 85011
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Expert Reply
gmatns2018 wrote:
Bunuel wrote:

The stem says that each term after the first two terms is the sum of the two immediately preceding terms. So, the seventh term \(s_7\) equals to the sum of the two immediately preceding terms, which are \(s_5\) and \(s_6\): \(s_7=s_6+s_5\).

If you consider the first term to be x and the second term to be y, then:
1st term = x;
2nd term = y;
3rd term = x + y;
4th term = y + (x + y) = 2y + x;
5th term = (x + y) + (2y + x) = 3y + 2x;
...


okay so i did this
6th term = 3x + 5y
7th term = 5x + 8y

St1 -- 6th - 4th = 5
3x + 5y - x - 2y => 2x + 3y = 5 --looks like x n y should be 1

St2 -- 6th + 7th = 21
3x + 5y +v5x + 8y => 8x + 13y = 21 --looks like x n y should be 1

could you please let me know why above is wrong ?


2x + 3y = 5 has INFINITELY MANY solutions. It's an equation with TWO unknowns. For example, x = 0 and y =5/3.
8x + 13y = 21 has INFINITELY MANY solutions. It's an equation with TWO unknowns. For example, x = 0 and y =21/3.
Intern
Intern
Joined: 05 Jan 2019
Posts: 14
Own Kudos [?]: 27 [0]
Given Kudos: 28
Location: Spain
GMAT 1: 740 Q49 V42
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Hi,

I am not able to understand why is not d).

When I first read the problem, the Fibonacci sequence instantly came to my mind: 0,1,2,3,5,8,13,21...
The only way I found to start the sequence having the 6th and 7th terms summing up 21 is starting by 0. Therefore I know that 5 is my solution as it is the 5th term.

That (probably incorrect) logic also validates the first statement.

Where am I making the mistake?

Please Bunuel help me! I want to be like you!
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [1]
Given Kudos: 85011
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
1
Kudos
Expert Reply
BunuelWannabe wrote:
Hi,

I am not able to understand why is not d).

When I first read the problem, the Fibonacci sequence instantly came to my mind: 0,1,2,3,5,8,13,21...
The only way I found to start the sequence having the 6th and 7th terms summing up 21 is starting by 0. Therefore I know that 5 is my solution as it is the 5th term.

That (probably incorrect) logic also validates the first statement.

Where am I making the mistake?

Please Bunuel help me! I want to be like you!


That's not the only sequence satisfying the stem and the second statement. For example, check 1, 1, 2, 3, 5, 8, 13, ...
Volunteer Expert
Joined: 16 May 2019
Posts: 3507
Own Kudos [?]: 6971 [1]
Given Kudos: 500
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
1
Kudos
Expert Reply
BunuelWannabe wrote:
When I first read the problem, the Fibonacci sequence instantly came to my mind: 0,1,2,3,5,8,13,21...

I also thought of the Fibonacci sequence, but you left out a crucial number in the beginning: 0, 1, 1, 2, 3, 5, 8, 13, 21... After the first two terms, the sum of the two previous terms is the value of the next term, just as we see in the question above, only this sequence starts with the first 1 instead of 0. I am guessing the question-writer had some fun with this one.

(Love the Feynman photo, by the way.)

- Andrew
Senior Manager
Senior Manager
Joined: 05 Jan 2024
Posts: 421
Own Kudos [?]: 285 [0]
Given Kudos: 102
Location: India
Concentration: General Management, Strategy
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
b2bt wrote:
Lets assume the first two terms to be x and y
Then rest of the numbers in the series will be x, y, x+y, x+2y, 2x+3y, 3x+5y, 5x+8y, ...

A.) (3x+5y) - (x+2y) = 5
2x+3y = 5 which is indeed the fifth term

SUFFICIENT

B.) (3x+5y) +(5x+8y) = 21
8x+13y = 21
its the 8th term

INSUFFICIENT

Answer - A
Difficulty - 650
Time taken - 1:59

­isn't x = y = 1 satisfies 2nd condition? Please correct me if anything is wrong? 
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [0]
Given Kudos: 85011
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Expert Reply
Purnank wrote:
b2bt wrote:
Lets assume the first two terms to be x and y
Then rest of the numbers in the series will be x, y, x+y, x+2y, 2x+3y, 3x+5y, 5x+8y, ...

A.) (3x+5y) - (x+2y) = 5
2x+3y = 5 which is indeed the fifth term

SUFFICIENT

B.) (3x+5y) +(5x+8y) = 21
8x+13y = 21
its the 8th term

INSUFFICIENT

Answer - A
Difficulty - 650
Time taken - 1:59

­isn't x = y = 1 satisfies 2nd condition? Please correct me if anything is wrong? 

­Have you cheked this post?

https://gmatclub.com/forum/in-the-seque ... l#p2210535­
Senior Manager
Senior Manager
Joined: 05 Jan 2024
Posts: 421
Own Kudos [?]: 285 [0]
Given Kudos: 102
Location: India
Concentration: General Management, Strategy
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Bunuel wrote:
Purnank wrote:
b2bt wrote:
Lets assume the first two terms to be x and y
Then rest of the numbers in the series will be x, y, x+y, x+2y, 2x+3y, 3x+5y, 5x+8y, ...

A.) (3x+5y) - (x+2y) = 5
2x+3y = 5 which is indeed the fifth term

SUFFICIENT

B.) (3x+5y) +(5x+8y) = 21
8x+13y = 21
its the 8th term

INSUFFICIENT

Answer - A
Difficulty - 650
Time taken - 1:59

­isn't x = y = 1 satisfies 2nd condition? Please correct me if anything is wrong? 

­Have you cheked this post?

https://gmatclub.com/forum/in-the-seque ... l#p2210535­

­Thanks, i was assuming x and y can only be integers. I was wrong there.
Math Expert
Joined: 02 Sep 2009
Posts: 94342
Own Kudos [?]: 640862 [1]
Given Kudos: 85011
Send PM
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
1
Kudos
Expert Reply
Purnank wrote:
­Thanks, i was assuming x and y can only be integers. I was wrong there.

­
Even then there are more solutions:
y = 9 and x = -12
y = 17 and x = -25
y = 25 and x = -38
...
GMAT Club Bot
Re: In the sequence S of numbers, each term after the first two terms is [#permalink]
Moderator:
Math Expert
94342 posts